Water intake and digestive metabolism of broilers fed all-vegetable diets containing acidulated soybean soapstock - Vieira,SL (2006)
A study was conducted to compare live performance and digestive metabolism of broiler chickens fed all-vegetable diets (All-Veg) compared to a regular diet including animal by-products. Three feeds were formulated and provided to broilers according to the feeding program: pre-starter from 1 to 10 days, starter from 11 to 21 days, and grower from 21 to 35 days. All feeds had corn and soybean meal as major ingredients; however, two of them were all-vegetable diets having either Degummed Soybean Oil (DSO) or Acidulated Soybean Soapstock (ASS) as fat sources. The third diet included poultry by-product and poultry fat. A total number of 360 day-old broiler chicks were allocated to 1m² battery cages, 10 chicks in each, and 12 replicates per treatment. Live performance was similar between groups of birds receiving the different diets with the exception of weight gain, which was increased for birds fed the All-Veg diet with ASS. Birds fed All-Veg diets had increased water intake and produced more excreta with a concurrent reduced feed metabolizability at both ages, regardless of fat source. Metabolizable Energy was not different for the three diets.